Análise comparativa do uso do concreto autoadensável e do concreto convencional em obras verticais - Costa, Ada Catarina Soares de Sena (2017)
Self-compacting concrete (SCC) is an evolution of conventional concrete (CV C ), and although there are several studies that prove its technical and economic feasibility in several places and types of work, this is not certain for vertical buildings in Fortaleza/ CE. It is known, however, that it is in the interest of the builders to use this technology, provided that its feasibility is proven. Therefore, it is justified the need to obtain loca l data about the technical and economic advantages of the use of this technology, as a way of boosting its production and consumption. In this sense, the present research aims to compare the use of SCC in relation to the CV C in works of vertical bu ildings executed in Fortaleza/ CE by means of two case studies. For that, a trace of SCC was developed in the laboratory, through its validation in a concrete plant until its use in the works. The CV C was replaced by SCC in two works. Noise, time, costs, quantity o f manpower and machinery and tools were measured during concretions , and it is necessary to use performance indicators, established from these parameters, to compare the concrete types in question. The SCC made it possible to reduce the labor force and the machinery and tools used in concretes, while also promoting the improvement of their productivity. There was noticeable noise reduction on the slab and labor costs, due to the waiving of the use of the immersion vibrator for the densification of the SCC . The cost of SCC per cubic meter was higher than CVC, however, the cost of SCC per MPa decreased as the compressive strength of the concrete increased. In a simulation made with the results obtained and considering only labor and material costs, the SCC wou ld need to be at most R $ 11.13 more expensive than the CV C for the characteristic compressive strength of 30 MPa, and only R $ 4.56 more expensive for the resistance of 35 MPa, so that the costs for both technologies were equivalent.